A Multicentre Randomized Controlled Trial of Recombinant Interferon-Alpha-2a in the Treatment of Patients with Chronic Hepatitis C - Masafumi Komatsu; Tsuyoshi Ono; Ko Nakajima; Itaru Toyoshima; Mitsuro Chiba; Osamu Masamune; Shunji Ohkubo; Tsukasa Yoshida; Hitoshi Yagisawa; Kanji Komatsu; Hideki Wakamatsu; Nobuo Yamada; et al. (Canadian Journal of Gastroenterology)
Sixty-one chronic hepatitis C patients were randomly assigned to receive either 6x106 or 9x106 U of recombinant interferon-alpha-2a (IFNα-2a) six days a week for the first two weeks of treatment, followed in both cases by 6x106 U three days a week for the next 22 weeks. In the low dose group, 11 patients showed a complete response maintained for at least six months, 12 responded but then relapsed and nine did not respond; the corresponding figures in the high dose group were 10, 15 and five patients, respectively. The differences between groups are not statistically significant. Thus, this study provides no evidence of therapeutic benefit from increasing the initial dose of IFNα-2a. In both treatment groups, complete responders had significantly lower pretreatment viral titres than nonresponders and were significantly more likely to be infected by type 2a versus type 1b virus.